TRADISI NISFU SYA’BAN DI DESA LUMBANG KECAMATAN SAMBAS KABUPATEN SAMBAS PADA TAHUN 1990-2024 - Unzira; Risa; Sri Sunantri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
ABSTRACT Nisfu Sya'ban is the middle of the month of Sya'ban in the Hijri year. The night of Nisfu Sya'ban is a special night because on that night humans are encouraged to worship a lot and do good. The focus of the problems studied in this study are (1) how the Nisfu Sya'ban tradition is carried out in Lumbang Village. (2) what are the meanings contained in the Nisfu Sya'ban tradition in Lumbang Village. (3) how do people view the Nisfu Sya'ban tradition in Lumbang Village. The approach used is a qualitative approach. This type of research is field research. The research location is in Lumbang Village, Sambas District, Sambas Regency. Data collection uses interview, observation, and documentation methods. The data sources obtained consist of primary data sources and secondary data. The results of this study indicate that: (1) the implementation includes a series of activities such as cleaning the grave by the syeh kubur, reading the Yasin letter three times, tahlil, Nisfu Sya'ban night prayer, and eating together. In addition, there is a tradition of sharing food that has changed from traditional cakes to snacks, as well as grave pilgrimage or